1995
DOI: 10.1159/000201231
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-Like Peptide-1 and Glucose-Dependent Insulin-Releasing Polypeptide Plasma Levels in Response to Nutrients

Abstract: The nutrient-dependent glucagon-like peptide-1 (7-36) amide (GLP-1) release was studied in comparison to the glucose-dependent insulin-releasing polypeptide (GIP) response in 10 healthy volunteers each undergoing various protocols. Plasma samples were saved up to 120 min after challenges by oral, intravenous or intraduodenal administration of nutrients. Basal plasma-GLP-1 concentrations ranged between 0.4 and 1.4 pM, maximal postprandial GLP-1 levels peaked between 10 and 12 pM. Intravenous glucose (25 g i.v.)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
360
8
9

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 518 publications
(385 citation statements)
references
References 29 publications
6
360
8
9
Order By: Relevance
“…Three g/kg of glucose or water (~100µl) were injected over 30 seconds into the stomach catheter. For hormonal determinations, portal blood was collected after 15 minutes (considered as the time point giving the highest value of the time course (Herrmann et al, 1995)) onto a mixture of 1µg/ml of aprotinin and 0.1mM EDTA. The portal blood was sampled as previously described (Cani et al, 2006); 250µl of blood can be easily sampled using this technique.…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%
“…Three g/kg of glucose or water (~100µl) were injected over 30 seconds into the stomach catheter. For hormonal determinations, portal blood was collected after 15 minutes (considered as the time point giving the highest value of the time course (Herrmann et al, 1995)) onto a mixture of 1µg/ml of aprotinin and 0.1mM EDTA. The portal blood was sampled as previously described (Cani et al, 2006); 250µl of blood can be easily sampled using this technique.…”
Section: Glucose Tolerance Test (Gtt)mentioning
confidence: 99%
“…Most studies have focused on responses to an oral glucose tolerance test, after which levels of GIP, GLP-1, and insulin rise, whereas glucagon levels are suppressed (4,18,20, 24). It is also known that fat and protein ingestion stimulate GLP-1 and GIP secretion (10,14,20,27). Less is known, however, regarding relationships between the incretin responses and changes in insulin and glucagon levels after meal or noncarbohydrate macronutrient ingestions.…”
mentioning
confidence: 99%
“…A study showed that high protein food intake increases the concentration of GLP-1 [79]. Cleavage of the preproglucagon resulted into two main bioactive forms of GLP-1, GLP-1 and the GLP-1 7-37 [80]. Both forms have a short biological half-life, because both of them are rapidly degraded during circulation by dipeptidil peptidase 4 (DPP4) [81].…”
Section: Glucagon-like Peptide-1mentioning
confidence: 99%